Teaching for Global Citizenship with Young Adult Literature in the Social Studies - Casey Holmes (Educational Considerations, 2019)
The rapid increase in communicative and technological integration through the late 1990s and early 2000s has reanimated the discussion surrounding the need to prepare young people to be global citizens. While the exact definition of global citizenship is difficult to pinpoint, the global community has identified several competencies that comprise responsible global citizenship. Although this idea has not yet saturated the American educational system, it will now be tested on an international scale when the Organisation for Economic Co-Operation conducts the Programme for International Student Assessment (PISA) this year. When the 2018 results are published in 2019, “global competence” will be the standard by which nations across the globe are compared to one another. The historical purposes of education in the United States and the specific disciplinary purposes of the social studies to educate knowledgeable and participation-ready citizens provides a prime opportunity for teachers to help students develop essential competencies of global citizenship. One particular instructional technique for developing a vision of global citizenship is the inclusion of young adult literature into the social studies classroom, which allows students to recognize the universality of the human experience regardless of background, culture, language, or religion. Young adult literature also serves as a medium for counter-storytelling as students develop personal connections with literature and the characters within them, particularly as they read stories of people whose experiences are often otherwise underrepresented in media and text.
Keywords: social studies; global citizenship; young adult literature; global competence